Multimodal therapy is feasible in elderly anal cancer patients. (2nd January 2017) - Dale, Jon Espen; Sebjørnsen, Sigrun; Leh, Sabine; Rösler, Cornelia; Aaserud, Stein; Møller, Bjørn; Fluge, Øystein; Erichsen, Christian; Nadipour, Saied; Kørner, Hartwig; Pfeffer, Frank; Dahl, Olav
Abstract: Background: Many patients are diagnosed with an anal cancer in high ages. We here present the outcome after oncological therapy for patients above 80 years compared with younger patients. Materials and methods: A series of 213 consecutive patients was diagnosed and treated at a single institution from 1984 to 2009. The patients received similar radiation doses but with different techniques, thus progressively sparing more normal tissues. The majority of patients also had simultaneous [5-fluorouracil (5FU) and mitomycin C] or induction chemotherapy (cisplatin and 5FU). The patients were stratified by age above or below 80 years. Despite that the goal was to offer standard chemoradiation treatment to all, the octo- and nonagenarians could not always be given chemotherapy. Results: In our series 35 of 213 anal cancer patients were above 80 years. After initial therapy similar complete response was observed, 80% above and 87% below 80 years. Local recurrence rate was also similar in both groups, 21% versus 26% (p = .187). Cancer-specific survival and relative survival were significantly lower in patients above 80 years, 60% and 50% versus 83% and 80%, (p = .015 and p = .027), respectively. Conclusion: Patients older than 80 years develop anal cancer, but more often marginal tumors. Even in the oldest age group half of the patients can tolerate standard treatment by a combination of radiation and chemotherapy, and obtain a relative survival of 50% after five years. Fragile patients not considered candidates for chemoradiation may be offered radiation or resection to control local disease.